Robust control for nonhomogeneous Markov jump processes: An application to DC motor device - Yin, YanYan; Shi, P.; Liu, F.; Lim, C. (Elsevier, 2014)
This paper studies the problem of robust H8 controller design for a class of uncertain Markov jump systems with time-varying transition probabilities, which follows nonhomogeneous jump processes. The time varying transition probability matrix is described as a polytope set. By Lyapunov function approach, under the designed controller, a sufficient condition is presented to ensure that the resulting closed-loop system is stochastically stable and that a prescribed H8 performance index is satisfied. Finally, an application of a DC motor device is addressed to demonstrate the effectiveness of developed techniques. © 2014 The Franklin Institute.